Integrasi Nilai-Nilai Islam Dan Budaya Mandailing Dalam Pembentukan Karakter Peserta Didik Di Sekolah - Laila Nasmi; Putri Yolanda Siregar; Putri Yolanda Siregar; Maya Sari; Nurhakikah; Khoirunnisa Lubis (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Education is a process that not only focuses on the transfer of knowledge, but also on the formation of personality and character of learners to become human beings with noble and cultured character. In the context of basic education in Indonesia, religious values and local culture have an important role as a moral foundation that guides children's behavior from an early age. This research aims to examine how the integration of Islamic values and Christmas Mandailing culture can be applied synergistically in the process of character formation of students in elementary school. Islamic values such as honesty, trust, responsibility, discipline, and compassion are the main guidelines in the daily lives of students. Meanwhile, the Natal Mandailing culture that is rich with the philosophy of Dalihan Na Tolu namely the principle of mutual respect, mutual help, and maintaining social harmony gives a great contribution to the formation of children's social and spiritual character. This research uses a qualitative approach with a literature study method, which examines various literature, books, and previous research related to character education based on religious values and local culture. The research results show that the integration of Islamic values and Mandailing Natal culture in learning activities, religious activities, and social interaction in the school environment can foster religious attitudes, manners, solidarity, and responsibility in students. In addition, these values also strengthen the local identity and enrich the child's personality so that it remains rooted in regional culture but is open to global development. Thus, the integration of Islamic values and Mandailing Natal culture becomes an effective strategy in creating a religious, humanistic, and characterful educational environment in elementary schools